2002
DOI: 10.1007/s10096-002-0773-6
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Urinary Tract Infection due to Pichia ohmeri

Abstract: In recent years, an increase in the number of nosocomial infections due to yeasts has been observed. Although Candida is the genus most frequently isolated from these infections, other yeasts such as Blastoschizomyces, Geotrichum, Trichosporon, Rhodotorula and Pichia species are being found more frequently [1,2]. Species belonging to the genus Pichia, especially Pichia anomala, have rarely been involved in human infections [3,4], and Pichia ohmeri has been reported as a human pathogen in only three previous ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported to cause outbreak in paediatric intensive care unit [11]. Although majority of cases reported are fungemia (as in the indexed patients), infections of other sites have also been documented [2, [12][13][14][15][16][17][18]. We reported a case of funguria due to K. ohmeri in a diabetic patient earlier [13].…”
Section: Discussionmentioning
confidence: 98%
“…K. ohmeri is a yeast known to cause invasive infections [3]. In the literature, we identified 73 cases of fungemia due to K. ohmeri [2, 4, 5], 2 cases of peritonitis [6, 7], 3 cases of endocarditis [810], one case of urinary tract infection [11], one case of cellulitis [12].…”
Section: Discussionmentioning
confidence: 99%